A phase‐retrieval toolbox for X‐ray holography and tomography. (14th April 2020) - Lohse, Leon M.; Robisch, Anna-Lena; Töpperwien, Mareike; Maretzke, Simon; Krenkel, Martin; Hagemann, Johannes; Salditt, Tim
Abstract : This article describes scientific software made publicly available for phase retrieval in X‐ray propagation imaging. The package is called HoloTomoToolbox and comprises a set of algorithms for phase retrieval in the direct‐contrast regime, as well as in the holographic regime, which is used for high‐resolution cone‐beam synchrotron recordings. Further to this, a set of routines is included to facilitate the conversion of the 2D phase projections in a 3D tomogram. Abstract : Propagation‐based phase‐contrast X‐ray imaging is by now a well established imaging technique, which – as a full‐field technique – is particularly useful for tomography applications. Since it can be implemented with synchrotron radiation and at laboratory micro‐focus sources, it covers a wide range of applications. A limiting factor in its development has been the phase‐retrieval step, which was often performed using methods with a limited regime of applicability, typically based on linearization. In this work, a much larger set of algorithms, which covers a wide range of cases (experimental parameters, objects and constraints), is compiled into a single toolbox – the HoloTomoToolbox – which is made publicly available. Importantly, the unified structure of the implemented phase‐retrieval functions facilitates their use and performance test on different experimental data.